Two additional treefrogs of the Boophis ulftunni species group (Anura: Mantellidae) discovered in rainforests of northern and south-eastern Madagascar - Köhler, Jörn; Glaw, Frank; Vences, Miguel (Zootaxa, 2008)
We describe two new frog species of the endemic Malagasy-Comoroan genus Boophis. One species, described as Boophis baetkei sp. n., originates from Forêt d’Ambre Special Reserve in northernmost Madagascar, whereas Boophis lilianae sp. n. was discovered near Ifanadiana and Ranomafana in the Southern Central East of the island. Both new species have very deep genetic divergences in the 16S rRNA gene that complicate the assessment of their phylogenetic affinities but are here tentatively assigned to the recently defined Boophis ulftunni species group based on phenetic similarity and preliminary results of analyses of other genes. All three species known in this group share a green dorsum with translucent shade in life, a pigmented venter and, most characteristic, pink markings in life and in preservative. Boophis lilianae sp. n. is the smallest species of Boophis known so far (SVL of adult male 18.3 mm, ovigerous female 20.0 mm). Phylogenetic relationships, distribution and threat status of the new species are discussed.